A Novel SM-Based MIMO System With Index Modulation - Aydin, Erdogan; Ilhan, Haci (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2016)
Multiple-input multiple-output systems with spatial modulation (MIMO-SM) have been recently proposed for high data rate, low complexity transmission schemes. However, in the SM, the antenna of the transmitter is randomly activated by the spatially modulated information bit sequence. Due to bad conditions of the active antenna's channel determined by the SM technique, the system would be likely to transmit frame with errors. This causes a significant reduction in the system performance. In this letter, to eliminate the bad effects of the channel assignment of the SM, we propose a novel SM-based MIMO system with index modulation technique (SM-MIMO-IM) when operating over i.n.d. and i.i.d. Rayleigh fading channels. The average symbol error rate (SER) and bit error rate (BER) of the proposed scheme are derived. It can be seen from numerical results that SM-MIMO-IM provides significant performance improvements and additional diversity gain compared to the classical SM and other some techniques given in the literature. Furthermore, the proposed mathematical analyses have been verified through the Monte-Carlo simulations.
Keywords: MIMO systems; spatial modulation; index modulation; symbol error rate; bit error rate; Telecommunications